(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
The article explores key aspects of linguistic relationships and basic language units from the perspective of systemic analysis. Special attention is given to three types of relationships: paradigmatic, syntagmatic, and hierarchical, which define the organization of language as a communicative system. Particular focus is placed on the interaction of invariants and variants, as well as the combinations of linguistic units in speech. The article presents a deep analysis of the mechanisms that ensure the integrity and functioning of the linguistic system. This approach allows for the identification of the structure of language based on invariants and variants of linguistic elements